Techno-Economic Evaluation of Hyaluronic Acid Production Through Extraction Method using Yellowfin Tuna Eyeball - Sheren Hana Elia; Brigitta Stacia Maharani; Intan Yustia; Gabriela Chelvina Santiuly Girsang; Asep Bayu Dani Nandiyanto; Tedi Kurniawan (ASEAN Journal of Science and Engineering, 2023)
The purpose of this study is to determine the feasibility of a hyaluronic acid fabrication project by extraction and isolation of the fish eyeball, and we evaluated the results from an engineering and economic perspective. Engineering analysis was analyzed based on tools and raw materials that are available on e-commerce. The economic analysis was done using several economic parameters, such as gross profit margin, the length of time required for an investment to return the total initial expenditure, the condition of a production project in the form of a production function in years, project benefits, and so on. The production of Hyaluronic Acid nanoparticles has good prospects. Technical analysis of producing 50.4 g/L of Hyaluronic Acid nanoparticles per day shows the total cost of the equipment purchased to be 20,726 USD. The investment will be profitable after more than four years and compete with the capital market standard. To ensure the feasibility of a manufacturing project, the project is estimated from ideal conditions to the worst conditions in production activities, including raw materials, utilities, sales, labor, and external conditions. The project is prospective and profitable in the small-scale industry, confirmed by positive values in all economic parameters).